Lab Tracer- The Remote Desktop Technology - Midhya Mohan, E; Mathew, Filma; George, Glemin; Harikrishnan, V; Benny, Vaneza; Bineesh, M (International Journal of Computer Sciences and Engineering, 2014)
Lab Tracer is a remote desktop technology that serves as the future of computer applications. The main objective is to develop an application that can control a computer remotely. Remote desktop technology makes it possible to view another computer’s desktop on our computer. The person sitting on the server can view and control the client’s computer. With fast, reliable, easy-to-use pc from remote control software, it helps us to save hours of running up and down the stairs between computers. The basic idea behind this work is to capture the screenshot of the client and send to the server. In response, mouse events and key events are captured from the server and exchanged those events between the Server and the Client via network.